Factors associated with the treatment outcomes of pulmonary tuberculosis patients enrolled in TB-DOTS Centers in the City of Manila: a cross-sectional study - Caronongan, Eunice Andrea T.; Cuaresma, Eumir Andres I.
The Philippines is one of the top countries with the highest tuberculosis burden in the world. To address this, Directly Observed Treatment Short-course (DOTS) is the core framework used by the National Tuberculosis Control Program (NTP). However, despite efforts to ensure patient compliance in TB-DOTS centers, there are still thousands of cases resulting in unsuccessful outcomes.